Primary Study on Effect of Extraction Methods on the Properties and Activities of Polysaccharides from Geum japonicum var. Chinense F. Bolle - Xuan Chen; Ying-Bo Liu; Yong Deng; Jian-Yong Zhang (Molecules)
Geum japonicum Thunb. var. Chinese F. Bolle, a traditional Miao medicine with significant clinical potential, is rich in polysaccharides. Despite its importance, there is a scarcity of research on the structure and activities of these polysaccharides. In this study, polysaccharides from Geum japonicum (GJPs) were extracted using various methods, including heated reflux extraction (HRE), acidic extraction (ACE), alkaline extraction (AAE), microwave-assisted extraction (MAE), enzymatic extraction (EAE), pressurized liquid extraction (PLE), and deep eutectic solvents extraction (DESE). The extraction yield, physicochemical properties, structural characteristics, and antioxidant activities of these polysaccharides were comprehensively investigated and compared. Physicochemical analysis, including FT-IR spectral features and monosaccharide compositions, revealed that the GJPs are acidic heteropolysaccharides with both α- and β-configurations. DESE and ACE were the most effective methods for obtaining the highest neutral and acidic sugars with yields of 29.1%/64.2%, and 39.8%/55.6%, respectively. Meanwhile, AAE was preferable for extracting the polysaccharide–protein complex, achieving a yield of 14.21% and exhibiting superior thermal stability. In particular, DESE and PLE showed the best homogeneity with distinct molecular weights of 39.5 kDa and 17.6 kDa, respectively. In addition, biological evaluation indicated that DESE and MAE exhibited relatively stronger antioxidant activities as evidenced by DPPH and ABTS assays. Conversely, ACE demonstrated highest Fe2+ chelating ability but the lowest activity in DPPH and ABTS assays. Furthermore, the results of correlation analysis showed that the monosaccharides composition, protein and polyphenol content were significantly associated with the antioxidant activity. The choice of extraction method greatly affects the property and activity of G. japonicum polysaccharides. Polysaccharides extracted by deep eutectic solvents from G. japonicum show promise as natural antioxidants in the food and medicine industries.